Randomized controlled trial of the impact on the outcome of pneumonia in children receiving Vitamin D supplementation - Dr. Jagadish K Jingi; Dr. Shailesh S Patil; Dr. Arunkumar S Desai (Pediatric Review: International Journal of Pediatric Research, 2018)
Objective: To study whether vitamin D supplementation in children presenting with pneumonia and severe pneumonia reduce its duration of recovery.Study design: Randomized, Double blind, Placebo-controlled trial.Setting: Paediatric unit of a Teaching hospital.Methods: 80 children between 2 months-5years with diagnosis of pneumonia and severe pneumonia (as per the WHO definition) admitted over a period of one year were included. Children with features of rickets, severe malnutrition, history of asthma, any underlying medical disorders and vitamin D supplementation over the last 12months were excluded. Children were randomized to two groups, Intervention group received 300,000 IU of Vitamin D (1ml) and the control group received 1ml of Sterile water as a placebo intramuscularly along with antibiotics and supportive care. Children were monitored for the resolution of symptoms. The two groups were comparable for baseline demographic, socioeconomic, clinical and laboratory parameters.Results: There was no significant difference in time to resolution of symptoms (fever, tachypnea and chest retractions) in Intervention group (3.63±1.27 days) & placebo group (3.6±0.78 days), p=0.933).Conclusion: Supplementation of single high dose (300,000 IU) of vitamin D given intramuscularly have no beneficial effect on the resolution of pneumonia and severe pneumonia in the children of 2 months to 5years of age.